2022
DOI: 10.3389/fnagi.2022.905115
|View full text |Cite
|
Sign up to set email alerts
|

Growth Differentiation Factor 15 Regulates Oxidative Stress-Dependent Ferroptosis Post Spinal Cord Injury by Stabilizing the p62-Keap1-Nrf2 Signaling Pathway

Abstract: BackgroundSpinal cord injury (SCI) is a severe traumatic disorder of the central nervous system (CNS) that causes irreversible damage to the nervous tissue. The consequent hemorrhage contributed by trauma induces neuronal ferroptosis post SCI, which is an important death mode to mediate neuronal loss. Growth differentiation factor 15 (GDF15) is a cytokine that regulates cell proliferation, differentiation, and death. However, the specific role of GDF15 in neuronal ferroptosis post SCI remains unknown.Materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…NOX4 promotes ferroptosis in astrocytes through lipid peroxidation induced by oxidative stress by impairing mitochondrial metabolism in Alzheimer’s disease ( 24 ). Oxidative stress-dependent ferroptosis can be regulated by GDF15 post-spinal cord injury ( 25 ). It was also reported that the effects of nanomedicine in targeting ferroptosis and apoptosis can be enhanced by oxidative stress ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…NOX4 promotes ferroptosis in astrocytes through lipid peroxidation induced by oxidative stress by impairing mitochondrial metabolism in Alzheimer’s disease ( 24 ). Oxidative stress-dependent ferroptosis can be regulated by GDF15 post-spinal cord injury ( 25 ). It was also reported that the effects of nanomedicine in targeting ferroptosis and apoptosis can be enhanced by oxidative stress ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…GDF15 was significantly increased in neuronal ferroptosis and silencing GDF15 aggravated ferroptosis both in vitro and in vivo. In spinal cord injury mice, knockdown of GDF15 significantly exacerbated neuronal death, aggravated ferroptosis-mediated neuroinflammation, and restrained locomotor recovery [73].…”
Section: Transforming Growth Factor-beta (Tgf-beta) Modulations In Fe...mentioning
confidence: 94%
“…In summary, the two most critical targets for the inhibition of Ferroptosis initiation, xCT and GPX4, have been modulated by NRF2. It has also been shown that Nrf2 can be used to regulate Ferroptosis to treat neurodegenerative diseases ( Song and Long, 2020 ), delay the progression of diabetic nephropathy (DN) ( Li S. et al, 2021 ) and prevent acute lung injury due to intestinal ischemia/reperfusion ( Dong et al, 2020 ), and it has been found that proanthocyanidins ( Zhou et al, 2020 ), alginose ( Gong et al, 2022 ), metformin ( Wang H. et al, 2020 ), and growth differentiation factor-15 ( Xia et al, 2022 ) are all inhibited by NRF2. These materials have been found to inhibit Ferroptosis through the Nrf2 pathway to treat SCI, but the specific downstream target proteins and enzymes that these substances affect through the Nrf2 pathway to inhibit Ferroptosis to treat SCI have not been clearly investigated.…”
Section: The Basic Process Of Ferroptosis and Its Relation To Scimentioning
confidence: 99%
“…And the knockdown of GDF-15 significantly exacerbated Ferroptosis. Subsequent researchers have found that GDF-15 inhibits Ferroptosis by activating the p62-Keap1-Nrf2 signaling pathway, thereby improving motor recovery in SCI ( Xia et al, 2022 ). However, other modulatory effects of GDF-15 on Ferroptosis and neuroinflammation in the neurocloud after SCI remain uncertain, and therefore further studies on the modulatory effects of GDF-15 are needed in the future.…”
Section: Related Substances That Improve Sci By Inhibiting Ferroptosismentioning
confidence: 99%
See 1 more Smart Citation